ISAM: a Software Architecture for Pervasive Computing - Jorge Luis Victória Barbosa; Adenauer Corrêa Yamin; Iara Augustin; Cláudio Fernando Resin Geyer (CLEI Electronic Journal, 2018)
The Mobile Computing is a vision of future that promises to modify the way people work and interact today. It has emerged as a new field, distinct from conventional distributed computing by its focus on mobility and its consequence. The physical and logical mobility allows the creation of applications with news requirements: built-in mobility, adaptability and flexibility. So, software production for this global mobility is complex. Challenges include designing applications which service levels and available resources are unpredictable, and the behavior is variable in time and space. To provide a system architecture that simplifies the task of implementing the mobile applications with adaptive behavior is the objective of the ongoing ISAM Project. In order to achieve its goal, ISAM uses as strategies: (a) integrated environment that provides a programming paradigm and its execution environment; (b) uniform treatment of adaptation through multilevel collaborative model, in which both the system and the application contribute for that. The scheduling process – the core of ISAM architecture, manages this collaboration. Introducing HoloLanguage abstractions that express adaptability makes the control of adaptation by part of application. So, adaptation is not fully transparent to applications. In this paper, we present the main decisions used for designing the ISAM Architecture. We also introduce a first taxonomy for mobile applications with adaptive behavior.